Analisis Makna Konotatif dalam Seloko Adat Perkawinan Masyarakat Dusun Kebun Tanjung Jabung Barat - Febriyanti, Dilva; Karim, Maizar; Nurfadilah, Nurfadilah (DIKBASTRA: Jurnal Pendidikan Bahasa dan Sastra, 2025)
Seloko as an oral tradition in Jambi Malay traditional weddings in Kebun Hamlet not only functions as a language aesthetic, but also as a medium for transmitting cultural values. This study aims to uncover the connotative meanings contained in the traditional wedding seloko, which have not been widely explored in cultural linguistic studies. This study uses a qualitative approach with a hermeneutic method. Data in the form of seloko texts were collected through non-participant observation, video documentation of the wedding process on December 8, 2024, and semi-structured interviews with traditional leaders. Data were analyzed through reduction, presentation, and interpretive conclusion techniques, with data validity tested through triangulation of sources and methods. This study reveals complex connotative meanings in four main processions. (1) Ulur Antar Serah Terimo Adat and Lembago mean responsibility and commitment; (2) Ulur Antar Serah Terimo Pengantin means resilience and togetherness in the household; (3) Buka Lanse means sacredness, learning, and openness; (4) Tunjuk Ajar Tegur Sapo means advice and trust. The natural and cultural symbols in the seloko represent the integration of spiritual, social, and ecological values ​​of the Jambi Malay community. In traditional marriages, the seloko serves as a multidimensional cultural communication system, serving not only as a guideline for married life but also as a mechanism for preserving local wisdom. This research emphasizes the importance of a hermeneutic approach to understanding the flexibility and dynamics of meaning in oral traditions amidst social change.